An overview of observability of linear control systems on time scales - Miranda, Francisco (2015)
Developments of observability of control systems on time scales are presented. Certain conventional dynamic models are described in the two parallel areas: continuous and discrete times. The results obtained in these two theories produce similar conclusions, but require diferente techniques for solving them. In 1988, Time Scales Calculus introduced by Stefan Hilger in his Ph.D. thesis, had the purpose to initiate an unification of the continuous and discrete time cases. This theory seems to be an ideal tool to create a unified technique. Since that time, many classical results of observability were extended to this new theory and applied in mixed time control systems. In this chapter is presented an overview of these results for linear control systems.